SEMIOTIC ANALYSIS OF THE DRAMA SCRIPT BULAN BUJUR SANGKAR BY IWAN SIMATUPANG - Hizkia Dwi Prayoga; Rangga Aria Hidayat; Robby Dwi Prasetia; Adita Widara Putra (Media Inovasi Pendidikan dan Publikasi, 2024)
This research aims to find semiotic elements contained in the play Bulan Bujur Sangkar by Iwan Simatupang. The data obtained comes from conversations and actions performed by the actors in the play. The whole semiotic element is the fact that language is not only oral but can be created with signifiers and signs. By utilizing Peirce's theory that describes icons, indices, and symbols, it is easier for readers to understand the meaning in the play. Iwan Simatupang's Bulan Bujur sangkar drama script has a hidden message that being someone who is able to fortify yourself so as not to fall into wrongdoing. The data generated in the form of quotations in the form of words or behavior that contain semiotics in communication. Qualitative research with descriptive method is the way used in analyzing this research. The results of the drama analysis contain semiotic elements used in conveying a certain intention by the actors of the drama.